Leading Issues in Competition, Regulation and Development 2004
DOI: 10.4337/9781845420659.00019
|View full text |Cite
|
Sign up to set email alerts
|

Ethical trade: issues in the regulation of global supply chains

Abstract: Ethical trade -initiatives that seek to improve the social and environmental impacts of global supply chains -is growing because of perceived shortcomings in globalisation and in traditional forms of state regulation. This paper analyses and categorises stakeholders, incentives and mechanisms of ethical trade. On the basis of current (limited) evidence, it summarises the impact of ethical trade via six performance measures: existence, extent, expedience, effectiveness, efficiency, and externalities. The mixed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
3
0
2
Order By: Relevance
“… Indirect: this represents a very large category of ICT applications in organisations in which the poor have no direct connection with the ICT, but in which the ICT application does deliver some benefit. Examples might include the use of ICTs to provide ethical and fair trade information which then drives better working terms and conditions to poorly-paid factory or farm workers (Heeks & Duncombe 2004, Light 2010, and the use of ICTs in large firms to improve supply, distribution and marketing to base-of-the-pyramid markets (Subrahmanyan & Gomez-Arias 2008, Chickweche & Fletcher 2013.…”
Section: Non-usementioning
confidence: 99%
“… Indirect: this represents a very large category of ICT applications in organisations in which the poor have no direct connection with the ICT, but in which the ICT application does deliver some benefit. Examples might include the use of ICTs to provide ethical and fair trade information which then drives better working terms and conditions to poorly-paid factory or farm workers (Heeks & Duncombe 2004, Light 2010, and the use of ICTs in large firms to improve supply, distribution and marketing to base-of-the-pyramid markets (Subrahmanyan & Gomez-Arias 2008, Chickweche & Fletcher 2013.…”
Section: Non-usementioning
confidence: 99%
“…114‐115). Subsequent studies by Heeks and Duncombe () concluded that while there have been some successes in ethical trade initiatives leading to improvements in health and safety conditions, the majority have little or no impact on poorer workers.…”
Section: Breaking the Impasse: New Directions For A Preventive Inclumentioning
confidence: 99%
“…114‐115). Dans des études ultérieures, Heeks et Duncombe () montrent que si certains projets menés dans le champ du commerce éthique ont réellement permis des améliorations de la SST, la majorité d'entre eux ont eu une incidence limitée ou nulle sur les travailleurs pauvres.…”
Section: Sortir De L'impasse: Nouvelles Orientations Pour L'instauratunclassified